Multi-layer graphene solar thermal absorber investigation with Ti-InAs-In2Se3 materials for thermal energy storage applications - Meshari Alsharari; Bo Bo Han; Ammar Armghan; Khaled Aliqab; Shobhit K. Patel (Case Studies in Thermal Engineering)
The development of solar energy offers a promising path to enhance various power generation processes through photonics techniques. Solar absorbers play a crucial role in maximizing solar energy utilization and are expected to remain a vital component of sustainable energy systems for many decades to come. Our research introduces a novel solar absorber structure based on Ti-InAs-In2Se3, enhanced with integrated graphene. The designed structure achieves 97.38 % absorption within 0.77–2.44 μm (990 nm bandwidth), 95.26 % within 0.7–2.5 μm (1800 nm bandwidth), and maintains an overall high efficiency of 93.28 % across a broad 2800 nm bandwidth. Machine learning combined with the finite element method (FEM) has been applied for the optimization of parametric analysis in the current work. The advanced absorber shows great potential for thermal energy applications and can be effectively utilized in various heating and cooling systems across agriculture, industry, and residential sectors, contributing to a more sustainable energy future.